Analisis Pembelajaran Pada Siswa ABK Dengan Ketunaan ADHD (Attention Deficit Hyperactivity Disorder) Di SDN Batuceper 1 Kota Tangerang - Nurfadhillah, Septy; Hasan, Najib; Ismawanti, Agnes; Akbar, Ahmad Alvinda (Peneliti.net, 2024)
The purpose of this study was to find out how the implementation of inclusion education services, especially ABK with ADHD disabilities held at SDN Batuceper 1 Tangerang City. The method used in this study uses a type of qualitative research with a descriptive method. The subjects of this study were inclusion guidance teachers, homeroom teachers, and grade 1 ADHD students. Data collection techniques include observation, interviews, tests, and documentation. Based on the results of an interview at SDN Batuceper 1.